The Relationship Between Teacher Creativity and Work Stress on the Performance of Generation X Elementary School Teachers in Facing Learning in the Digitalization Era - Julianti, Hani Tri; Mellita, Dina (Yayasan Sembilan Pemuda Indonesia, 2023)
Civil Servants in primary schools are dominated by teachers who have an age range of 46 – 57. Older teachers bring positive things to teaching, especially teaching experience and quality. But in the world of education, the positive influence of age has its limits. This means that where there is a point of age it no longer has a positive effect but a negative one. The purpose of this study was to determine the relationship between teacher creativity and work stress on teacher performance. In this study using primary data and secondary data, primary data was obtained by distributing questionnaires with a sample of 150 elementary school teachers in Banyuasin I. The data analysis technique used was Partial Least Square Structural Equation Modeling (PLS SEM) using the SMARTPLS application. From the results of data analysis, it was found that teacher creativity and work stress have a positive effect on employee performance. In addition, this study explains that teacher creativity and work stress will determine the increase in teacher performance.